Tourism Object Development and Improvement of Tourist Visit In Burake Tourism Object In Tana Toraja District - Muh. Rizal S; Muhammad Luthfi Siraj; Maya Kasmita (Pinisi Business Administration Review, 2020)
Tourism in Indonesia is experiencing growth but it still has to get the full attention of various parties. Research Objectives to determine the development of tourism in Burake tourism objects and to find out how the level of tourist visit to Burake tourism objects. The results showed that the development of tourist attractions can increase tourist visits seen from the tourist anthesis where there is a main attraction of tourist attraction to come to visit the statue of Jesus as the main object besides that there is also the statue of the Virgin Mary, the glass adrenaling bridge which is the only item in Toraja, photo spots and natural scenery that are cool and beautiful to attract tourists. Marketing and Promotion that attracts tourist visits.